THE USE OF ARABIC CONSONANT SOUNDS TO ARRIVE AT ENGLISH PRONUNCIATION: A CASE STUDY ON INDONESIAN EFL STUDENTS IN TERTIARY LEVEL - Rosalin Ismayoeng Gusdian; Riski Lestiono (Universitas Brawijaya, 2018)
The intention of this study is to reveal how several Arabic consonant sounds are employed in teaching English pronunciation to Indonesian EFL students in university level. This study was conducted qualitatively as it constituted describing and analyzing the data without influencing them in any way. The research subjects were second-semester freshmen students who took Basic Speaking in English Language Education Department, University of Muhammadiyah Malang. Furthermore, participant observation in two consecutive meetings was conducted to gather the data. The findings have revealed 1) there are three Hijaiyah letters used to assist the students to produce correct pronunciation, namely ث, ذ, and ش which correspond /θ/, /ð/, and /ʃ/ respectively, 2) the techniques comprise reading a short passage, tongue twister game, the use of phonetic transcription, sound imitation, and pronunciation drill, and 3) the implementation of the aforementioned techniques was conducted consecutively, both before and after the introduction of Hijaiyah letters.